Asymmetry in Hedges, Safe Havens, Flights and Contagion: Unconditional Quantile Regression Approach - Meng-Shiuh Chang; Meng-Wei Chen; Peijie Ju (SAGE Open, 2023)
We examine the hedging/safe-haven ability of gold, the US dollar, bonds, crude oil, and Bitcoin against stocks using the unconditional quantile regression (UQR). We reveal that hedging (safe-haven) effect generally decreases (increases) with the quantiles of asset returns and find an asymmetric flight from stocks to the US dollar as well as asymmetric stock-gold, stock-bond, and stock-oil contagion. Finally, we find a connection between the asymmetric safe haven and asymmetric cross-asset flights/contagion. Therefore, investors seeking hedging and safe-haven assets and investigating flights or contagion should consider the feature of extremes of assets returns. JEL: C13; G11; G14